Antioxidant Activity in Extracts from Zingiberaceae Family: Cardamom, Turmeric, and Ginger - Pura Ballester; Begoña Cerdá; Raúl Arcusa; Ana María García-Muñoz; Javier Marhuenda; Pilar Zafrilla (Molecules, 2023)
An increase in life expectancy leads to a greater impact of chronic non-communicable diseases. This is even more remarkable in elder populations, to whom these become main determinants of health status, affecting mental and physical health, quality of life, and autonomy. Disease appearance is closely related to the levels of cellular oxidation, pointing out the importance of including foods in one’s diet that can prevent oxidative stress. Previous studies and clinical data suggest that some plant-based products can slow and reduce the cellular degradation associated with aging and age-related diseases. Many plants from one family present several applications that range from the food to the pharmaceutical industry due to their characteristic flavor and scents. The Zingiberaceae family, which includes cardamom, turmeric, and ginger, has bioactive compounds with antioxidant activities. They also have anti-inflammatory, antimicrobial, anticancer, and antiemetic activities and properties that help prevent cardiovascular and neurodegenerative diseases. These products are abundant sources of chemical substances, such as alkaloids, carbohydrates, proteins, phenolic acids, flavonoids, and diarylheptanoids. The main bioactive compounds found in this family (cardamom, turmeric, and ginger) are 1,8-cineole, α-terpinyl acetate, β-turmerone, and α-zingiberene. The present review gathers evidence surrounding the effects of dietary intake of extracts of the Zingiberaceae family and their underlying mechanisms of action. These extracts could be an adjuvant treatment for oxidative-stress-related pathologies. However, the bioavailability of these compounds needs to be optimized, and further research is needed to determine appropriate concentrations and their antioxidant effects in the body.